Complications of male circumcision in Iran: A systematic review and weighted averaged analysis - Arshadi, Hamid; Abedi, Akbar; Nematollahi, Shahrzad; Shojaeefar, Ehsan; Abbasi-Fashami, Mahta; Hosseini, Jalil (Archives of Men's Health, 2020)
Male circumcision (MC) is a minimal procedure to remove penile foreskin and is one of the oldest and most frequent surgical procedures in Iran, where the majority of the population identify themselves as Muslim. Despite numerous health benefits, MC is an issue of debate among pediatricians, urologists, and other medical professionals. Much of the debate stems from the lack of national guidelines and the incidence of minor or serious clinical complications. This study performed a systematic review on the current literature on male circumcision in Iran and summarized the major clinical complications reported by the studies.